Organisation et contrôle de l’espace dans l’aire culturelle aja-fon (Sud-Togo et Bénin – XVIIe-XIXe siècle) - Dominique Juhé-Beaulaton (Afriques)
Human migrations and the foundation of new villages led people to reckon with their environment, with the new territory and its occupants, by referring to the religious principles that underlay the social organization of Aja-Tado societies. Oral traditions, toponyms and writings by Europeans provide evidence about how this territory took shape out of a perception of this environment. The control of the natural environment exercised by the society led to its territorialization. Migrants or conquerors, depending on the context, adopted strategies that involved making matrimonial alliances and moving divinities so as to control a territory and its occupants. Among the Slave Coast kingdoms (Ouidah, Allada, Dahomey), a network of royal settlements, likewise associated with divinities, controlled the movement of people and goods, and thus asserted political authority over the whole territory.